2019
DOI: 10.1038/s41467-019-09955-8
|View full text |Cite
|
Sign up to set email alerts
|

A Mycobacterium tuberculosis surface protein recruits ubiquitin to trigger host xenophagy

Abstract: Ubiquitin-mediated xenophagy, a type of selective autophagy, plays crucial roles in host defense against intracellular pathogens including Mycobacterium tuberculosis (Mtb). However, the exact mechanism by which host ubiquitin targets invaded microbes to trigger xenophagy remains obscure. Here we show that ubiquitin could recognize Mtb surface protein Rv1468c, a previously unidentified ubiquitin-binding protein containing a eukaryotic-like ubiquitin-associated (UBA) domain. The UBA-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 69 publications
(129 reference statements)
1
94
0
Order By: Relevance
“…Finally, since Mtb is an exquisitely evolved pathogen, it is very likely that yet-to-be-identified bacterial proteins are intimately involved in these processes. Indeed, the recent discovery of a ubiquitin-binding protein (Rv1468c) on Mtb's surface suggests that Mtb does have mechanisms for modulating the host's selective autophagy pathway (Chai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, since Mtb is an exquisitely evolved pathogen, it is very likely that yet-to-be-identified bacterial proteins are intimately involved in these processes. Indeed, the recent discovery of a ubiquitin-binding protein (Rv1468c) on Mtb's surface suggests that Mtb does have mechanisms for modulating the host's selective autophagy pathway (Chai et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…P62 and NDP52 are two classic receptors implicated in xenophagy. P62 assembles on the microbes as receptors once the cells were affected by pathogens, such as Salmonella [142] and mycobacteria [143]. NDP52 can be recruited as xenophagy receptors for Salmonella [144].…”
Section: Autophagy Receptors In Macrophagementioning
confidence: 99%
“…Xenophagy is a specific type of autophagy that explains the process of delivering intracellular pathogens to the lysosomes via autophagic mechanisms [68]. It has been reported that the cellular cargo protein ubiquitin recognizes surface proteins of Mtb and activates the host xenophagy process to control intracellular growth of Mtb [69,70]. Primarily autophagy is regulated by the mammalian target of rapamycin (mTOR) complex 1 and the adenosine monophosphate-activated protein kinase (AMPK) [71,72].…”
Section: Autophagy and Tbmentioning
confidence: 99%